Assessment of Financial Health Level at PT Jasa Marga Tbk for the Period 2020 – 2023 - Lestari, Miftah Yusti Anjar; Nugraeni, Nugraeni (Journal Research of Social Science, Economics, and Management, 2025)
This study aims to assess the financial health of PT Jasa Marga Tbk for the period of 2020-2023 based on the Ministry of State-Owned Enterprises Decree No. KEP-100/MBU/2002. The research analyzes various financial ratios, including profitability, liquidity, activity, and solvency, to evaluate the company’s performance. This study uses quantitative descriptive analysis that explains the results of the research in the form of financial statement data related to the company's performance. The findings indicate fluctuating financial health with improvements in profitability in 2023, but issues in solvency and activity ratios. The company’s profitability was below the standard in 2020-2022, with a significant increase in 2023. Liquidity ratios showed improvement, indicating the company’s better ability to meet short-term obligations. However, solvency and activity ratios exhibited instability. Overall, the financial health of PT Jasa Marga Tbk for the period 2020-2023 is categorized as "less healthy." This study provides valuable insights for further research and can serve as a reference for evaluating the financial health of other state-owned enterprises, considering all aspects of financial, administrative, and operational performance.